2004
DOI: 10.1073/pnas.0405109101
|View full text |Cite
|
Sign up to set email alerts
|

The 15-K neutron structure of saccharide-free concanavalin A

Abstract: The positions of the ordered hydrogen isotopes of a protein and its bound solvent can be determined by using neutron crystallography. Furthermore, by collecting neutron data at cryo temperatures, the dynamic disorder within a protein crystal is reduced, which may lead to improved definition of the nuclear density. It has proved possible to cryo-cool very large Con A protein crystals (>1.5 mm 3 ) suitable for high-resolution neutron and x-ray structure analysis. We can thereby report the neutron crystal structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 26 publications
(33 reference statements)
1
38
0
Order By: Relevance
“…Another beneficial effect of cryocooling originates from reduced dynamic disorder. For example, about twice as many water molecules are detected at cryo-temperature compared with room temperature in protein structures determined using X-ray (Nakasako, 1999) or neutron crystallography (Blakeley et al, 2004). Today, more than 90% of all macromolecular X-ray crystal structures are determined from data collected at 100 K (Garman & Owen, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Another beneficial effect of cryocooling originates from reduced dynamic disorder. For example, about twice as many water molecules are detected at cryo-temperature compared with room temperature in protein structures determined using X-ray (Nakasako, 1999) or neutron crystallography (Blakeley et al, 2004). Today, more than 90% of all macromolecular X-ray crystal structures are determined from data collected at 100 K (Garman & Owen, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Neutron diffraction offers a more reliable solution to the problem, because hydrogen and, particularly, its isotope deuterium (D) are visible at much lower resolutions than required with X-rays (14,15). The approach does present a number of challenges, particularly the need to cool the large crystals required for neutron crystallography down to the cryogenic temperatures required for the study of enzyme intermediates (16). But the fact that neutrons are non-ionizing and are scattered by the atomic nuclei (rather than by the electrons, as in X-ray crystallography) means that photoreductionwhich has been the source of most of the confusion in previous X-ray work -does not occur at all.…”
mentioning
confidence: 99%
“…However, we have recently shown that it is possible to freeze and collect high resolution X-ray (1.65 Å on a rotating anode) and neutron data (2.5 Å on LADI; Fig. 7) from large concanavalin A protein crystals ($2 and 5 mm 3 ) as examples (Blakeley, Kalb et al, 2004). These data have allowed a combined 'X + n' protein structure analysis to be undertaken as performed previously with room temperature X-ray and neutron data sets (Habash et al, 2000).…”
Section: Case Study: Cryo-and Room-temperature Concanavalin a Structuresmentioning
confidence: 99%
“…Bigger crystals for neutron structural studies are also needed and where they are reasonably perfect. In an interesting twist of this story, freezing of very large crystals of proteins suitable for high resolution neutron data collection is a recent breakthrough (Blakeley, Kalb et al, 2004). Neutron cryo-crystallography benefits the clarity of bound water structure, including the water deuteriums, and also opens up freeze-trap neutron protein structural studies.…”
Section: Introductionmentioning
confidence: 99%